A New Species of Sinarundinari (Bambuseae) from Nagaland, India - Naithani, H. B. (Indian Forester, 1994)
A species of Sinarundinaria new to science, Sinarundinaria nagalandiana Naithani,from Nagaland, India is described. This species is allied to Sinarundinaria griffithiana (Munro) Chao & Renv., but differs by culm sheaths without ligule and having broad nonconvexly truncate apex, leaves broader.